Husbands' and wives' diverging perceptions on who decides - Panu Poutvaara; Maximilian Schwefer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
An emerging literature highlights the importance of empowering women. Female decision-making power is typically measured by surveying only one partner, but the few studies surveying both have documented large differences in perceptions. We analyze these perceptions and their consequences, using survey data from Indonesia. Both male and female respondents systematically report a higher share of decision domains in which they decide. Female labor supply and contraception use are higher when both partners perceive female decision-making power in these domains. Increases in female income share are associated with increases in the perceived female decision-making power.
Keywords: J16; D13; J13; J22; C83; 330; Female decision-making power; intrahousehold allocation; family planning; female labor supply; discordance in household surveys